THE ROLE OF CREATIVITY IN ENGINEERING - SALIHI, ATEEQU MUSTAPHA (IJRDO -Journal of Computer Science Engineering, 2016)
Creativity in engineering education is an ongoing critical issue for universities, inthe sense that it helps meet the expectations for professional engineers, as well ascomplete the intellectual development of individuals. However, the importance ofimplementing creativity education in engineering education in the classroom has notbeen fully recognized. In this paper recent publications were reviewed in this regard,attempting to dissect what creativity means to engineers, and how they can overcomethe stumbling blocks to creativity. Having explored the creative process, wesuggested an operable tool based on Treffinger’s creative learning model that canbe implemented in a classroom setting to facilitate creativity.